The Worst to Best Hopes: An Appraisal of Pakistan-India Relations (Journal of Social Sciences Review, 2023)
The relations between Pakistan and India share a critical relations history. Both the neighboring states fought major three wars in 1965, 1971 and 1998 (Kargil) and numerous medium and small-level clashes due to a number of different causes. The study founds Kashmir as the root cause as well as Line of Control (LOC) issues, interference in each other country affairs, political criticism and religious issues have been observed as misunderstandings between both countries. However, the leadership of both nations have a history to solve these issues through peaceful means but yet failed.  This study relies on multiple sources i.e. primary and secondary through descriptive research methods. The study suggests that Pakistani and Indian delegates would do well to compromise their positions and build confidence between them as well as it will be necessary to retain some degree of flexibility with regard to the principles and points that are being negotiated.
Keywords: Pakistan, India, Kashmir, LOC, Terrorism